The impact of swimming and other aquatics on human development, physiology, and the course of some diseases - Wróblewski, Jakub; Kawecka, Weronika; Wróblewski, Wiktor; Zalewski, Paweł; Biłogras, Jan (Quality in Sport, 2024)
Introduction: In our work, we decided to connect physical activity and hydrotherapy as well as explore the impact of water-based physical activity on human organisms. We focused on the effects on physiology and body development. We also analysed studies that research aquatics activity as a method of treatment. We aim to present scientific evidence about using in-water activity in prevention and rehabilitation. Results: Physical activity in water has a beneficial influence on the cardiorespiratory system and can be used for both prevention and rehabilitation. It is well-tolerated among patients with chronic obstructive pulmonary disease even if physical comorbidities are present. Swimming can be used as a rehabilitation and even one form of asthma treatment in the paediatric population. Swimming can improve insulin sensitivity, glucose control and reduce biomarkers of endothelial activation. There is data suggesting that the water environment exercises benefit patients with rheumatological diseases like ankylosing spondylitis, rheumatoid arthritis, fibromyalgia and osteoarthritis. A positive impact was observed on the population suffering from ADHD and autism spectrum disorder. The diving by the Bathysmed® protocol seems to decrease symptoms of PTSD. Research conducted on the paediatric population shows that swimming training can benefit motor development. There were no observed impacts of aquatics on IgA levels. In contrast to that swimming can improve the level of TNFα and HSP70. Conclusions: Recent studies show a positive influence on human development, physiology, and the course of some diseases. They suggest that aquatics can be used as a form of preventing, rehabilitating and even treatment of some illnesses. The conclusions from recent studies need to be confirmed in further research because of their limitations.